Falling in love on Willow Creek - Mason, Debbie (Novelist) (Mason, Debbie (Novelist). Highland Falls novel., 2021)
In this latest Highland Falls romance, a single mom-to-be is rescued by an undercover FBI agent who makes her believe in love again.